Studies of cool giant stars using GHRS spectra - Jordan, C; McMurry, A (2001)
Observations with the GHRS have made a considerable impact on the study of cool stars. Observations with the International Ultraviolet Explorer established the overall nature of the UV spectra of cool evolved stars, but only strong sources could be observed at high resolution and measurements of line widths were impeded by the lower signal-to-noise, The greater sensitivity of the GHRS has allowed many more emission lines to be observed, in particular, weak lines of C IV and fluorescent lines of Fe II, HZ and CO in a Tau (K5 III). These and other examples of how GHRS observations have led to improvements in spectroscopy and understanding cool giant atmospheres are discussed.